Arsenopyrite Bio-Oxidization Behavior in Bioleaching Process: Evidence From Laser Microscopy, SEM-EDS, and XPS - Yin, Lu; Yang, Hong-ying; Tong, Lin-lin; Ma, Peng-cheng; Zhang, Qin; Zhao, Miao-miao (Frontiers in Microbiology, 2020)
In arsenopyrite bioleaching, the interfacial reaction between mineral and cells is one of the most important factors. The energy of the interface is influenced by the mineralogical and microbiological characteristics. In this paper, the interfacial energy was calculated and the surface of arsenopyrite during the bioleaching process was characterized by 3D laser microscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy, in order to assess the dissolution and oxidation behavior of arsenopyrite during bioleaching. The results showed that the contact angles of arsenopyrite were 22±2 ° when covered with biofilms, but the reaction surface of arsenopyrite turned 103±2 °. However, the angle was 45–50 ° when covered by passive layer, which was half as that of arsenopyrite surface. The interfacial energy of arsenopyrite without biofilms increased from 45 to 62 mJ/m2 while decreased to 5±1 mJ/m2 when covered by biofilms during the leaching process. The surface was separated into: fresh surface, oxidized surface, and (corrosion) pits. The interfacial energy was influenced by the fresh and oxidized surfaces. Surface roughness increased from 0.03±0.01 to 5.89±1.97 μm and dissolution volume increased from 6.31±0.47×104 to 2.72±0.49×106 μm3. The dissolution kinetics of arsenopyrite followed the model of Kt=lnX and the dissolution mechanisms were mixed controlled: surface reaction control and diffusion through sulfur layer. On the surface of arsenopyrite crystal, the oxidation steps of each element can be described as: for Fe, Fe(Ⅱ)–(AsS) → Fe(Ⅲ)–(AsS) → Fe(Ⅲ)–OH or Fe(Ⅲ)–SO; for S, As–S(-1) or Fe–S(-1) → polysulfide S → intermediate S–O → sulfate; and for As, As -1–S → As0 → As+1–O → As+3–O →As+5–O.